Income diversification in the German banking industry - Ramona Busch; Thomas Kick (Deutsche Bundesbank, 2009)
In the last few years it has been possible to observe decreasing interest margins for German universal banks. At the same time, institutions increasingly moved part of their business from interest to fee-earning activities. This study analyzes the determinants of non-interest income and its impact on financial performance and the risk profile of German banks between 1995 and 2007. We find empirical evidence that for all German universal banks risk-adjusted returns on equity and total assets are positively affected by higher fee income activities. Additionally, for commercial banks we show that a strong engagement in fee-generating activities goes along with higher risk. In order to analyze possible cross-subsidization effects between interest and fee business we also examine how banks' expansion in fee-based services has affected their interest margin. For savings and commercial banks we find that institutions with a strong focus on fee business charge lower interest margins when credit risk is controlled.
Keywords: G11; G21; G32; 330; Income diversification; interest income; fee income; interest margin; two-stage least squares estimator; Bankgeschäft; Diversifikation; Einnahmen; Zins; Honorar; Schätzung; Deutschland